2001
DOI: 10.1106/mmgh-xuag-hp5b-ytdg
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Water Mist Fire Suppression Technology: Part II-Application Studies

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 7 publications
2
41
0
Order By: Relevance
“…Compared to other types of fire, the fire size associated with the electric equipment is relatively small [10]. The primary concern in using a portable water mist extinguisher for firefighting is that the discharge of water mist toward energized targets may produce a shock hazard to the user.…”
Section: Class C Fire Scenarios and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other types of fire, the fire size associated with the electric equipment is relatively small [10]. The primary concern in using a portable water mist extinguisher for firefighting is that the discharge of water mist toward energized targets may produce a shock hazard to the user.…”
Section: Class C Fire Scenarios and Measurementsmentioning
confidence: 99%
“…Water mist systems, according to their applications, can be distinguished into three types: total compartment application (TCA), local application (LA) and zoned application (ZA) systems [10]. For a TCA system, water is discharged from all nozzles distributed throughout the compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh cooking oil was introduced into the pan and then heated continuously at [3][4][5] o C/min until it auto-ignited. After the flame had spread over the whole oil surface, the fire was allowed to burn freely for 30 s, which ensures that there is sufficient time for people to evacuate from the oil cooker before the activation of a suppression system, according to requirement of the test protocol [1].…”
Section: Test Facility and Proceduresmentioning
confidence: 99%
“…Water mist that consists of small water droplets (D v99 < 1000 µm) has been used to successfully extinguish various types of fires [3][4][5] as well as cooking oil fires in a commercial deep fat fryer without causing significant fire flare-up and re-ignition [6]. However, no research on usage of fine water mist against large cooking oil fires associated with the industrial oil cookers has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, water mist suppression systems have been used to replace halons for the protection of machinery spaces, ships and electronic equipment [13][14][15]. Water mist has also been used for applications where traditional technologies have not been effective [16,17]. For example, water mist fire suppression systems are used to extinguish flammable liquid fires that conventional sprinkler systems cannot extinguish due to splashing and spillage of the fuel.…”
Section: Introductionmentioning
confidence: 99%